The role of levatorplasty procedure in improving genital hiatus area and symptoms in pelvic organ prolapse with ballooning in Indonesia - Anggrainy Dwifitriana Kouwagam; Fernandi Moegni; Budi Iman Santoso; Suskhan Djusad; Surahman Hakim; Tyas Priyatini; Alfa Putri Meutia (Urogynaecologia International Journal)
Levatorplasty procedures can be performed in cases of pelvic organ prolapse (POP) with hiatal ballooning to reduce the risk of prolapse recurrence. At Dr. Cipto Mangunkusumo Hospital Jakarta, POP patients with hiatal ballooning during pre-operative ultrasound examination were planned for an additional levatorplasty procedure. However, there was no objective assessment such as the ballooning condition postoperatively. The objective of this paired comparative analytic study was to determine the improvement of ballooning after levatorplasty by assessing anteroposterior (AP) hiatal length and maximal levator hiatal (LHmax) on ultrasound Pelvic Organ Prolapse Quantification System, and the Pelvic Floor Distress Inventory (PFDI) Questionnaire-20. The data of 32 women were taken retrospectively and prospectively during 2021-2022 and statistically analyzed using SPSS 24.0. There was a reduced degree of ballooning measured by LHmax area in 28 patients (87.5%), AP hiatal length in 26 patients (81.25%), and genital hiatus + perineal body length in 25 patients (78.1%) and decreased median value of PFDI to 31.2 (p=0.009) after levatorplasty. The levatorplasty procedure has proven beneficial in improving the objective and subjective outcomes of POP patients with evidence of ballooning on ultrasonography.